Pelatihan Pengolahan Kotoran Kambing Menjadi Pupuk Organik Cair Dengan Pemanfaatan KOHE - Manaf Nur Arifin; Wirawan Fadly (Jurnal Pemberdayaan Masyarakat, 2022)
The majority of the people in Wonodadi Village have goat farms. The problem with goat farms that is felt by the community is the difficulty of processing goat waste. The community needs assistance to find the right solution in making efforts to process livestock waste so that it does not pollute the environment and can become a business product that is beneficial to the community. This community service aims to raise public awareness of creative living by processing animal waste into products that have economic value. The community service method is carried out with ABCD which further optimizes the potential from within and the physical assets of the environment. These potentials are agriculture and animal farms as a learning environment and environmental physical assets as learning resources. The stages in the ABCD Method are; discovery, dream, design, define, destiny, and reflection. The result of the activity is that there is an increase in the ability of goat farms as the target of activities to process goat waste into fertilizer. In conclusion, community empowerment activities through the manufacture of liquid organic fertilizer with the use of animal farms can overcome the problems faced by goat farms in processing waste which is not limited to producing fertilizer but has economic value.